Efektivitas Program Pengembangan Usaha Pangan Masyarakat (PUPM) dalam Meningkatkan Pendapatan Petani di Provinsi Sulawesi Tenggara - Muhammad Taslim; Idrus Salam; La Ode Alwi (Jurnal Sosio Agribisnis, 2019)
The studi was carried out in Bombana and Konawe Selatan districts from May to June 2019. The purpose of this study was to determine the effectiveness of the PUPM Program in increasing the income of farmers of Gapoktan members in Southeast Sulawesi Province. The method used in this study is a survey method using primary data and secondary data. Sampling is done by quota sampling. The analytical tool used is the calculation of the difference between the government purchase price (HPP) with the cost of production of rice farming, and comparing the income of farmers at various price levels. Based on the analysis results obtained the value of the Government Purchase Price (HPP) is smaller than the Cost of Production so that it is concluded that the determination of the HPP provides benefits to farmers members of Gapoktan, as well as the average income of farmers is shown that the value of grain sales at the Gapoktan level is greater than the value of grain sales at the collector level. Thus, it can be concluded that the PUPM Program is effective in increasing farmers' incomes.Keywords: effectiveness; government purchase price; cost of goods sold; income